Behavioral risk factors and effects of lifestyle modification on adults with diabetes: a Brazilian community-based study - Burini, Roberto Carlos; Torrezan, Gabriel Augusto; Portero, Kátia Cristina da Cruz; McLellan, Kátia Cristina Portero [UNESP] (My University, 2013)
Lifestyle is directly related to the incidence of type 2 diabetes mellitus (DM-2), a risk dramatically elevated by obesity and inactivity. Several studies have verified that educational interventions can delay the onset of DM-2. Some of the interventions strategies utilized medication and diet, diet and/or physical exercise or the combination of diet and exercise, generally referred to a change in lifestyle. Despite the evidence that DM-2 can be preventive, there is still limited availability of effective prevention programs. DM-2 is considered an emerging public health problem as it is estimated that by the year of 2030 there will be about 366 million people with diabetes worldwide. DM2 remains a leading cause of cardiovascular disorders and many other complications. Our intent with this paper is to present researches and strategies (diet and physical activity interventions) that successfully improved plasma glucose control as a result of an effective lifestyle intervention program.
Keywords: Obesity; Diabetes type 2